Soybean Varieties “Baraka”, “Madina”, And “Nafis” In Uzbekistan: Agronomic Characteristics, Productivity, And Adaptation Potential (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
Soybean (Glycine max L. Merr.) is one of the most important leguminous crops worldwide due to its high protein and oil content. In Uzbekistan, the cultivation of soybean has expanded significantly to improve food security, livestock feed production, and soil fertility. Among locally adapted soybean varieties, Baraka, Madina, and Nafis have attracted considerable attention because of their high productivity and adaptability to irrigated conditions. This review summarizes the biological characteristics, agronomic performance, yield potential, and cultivation prospects of these varieties under Uzbekistan's soil-climatic conditions. The analysis indicates that Baraka demonstrates stable grain yield and drought tolerance, Nafis is characterized by high protein content and adaptability to different ecological zones, while Madina possesses favorable agronomic traits suitable for intensive farming systems. These varieties contribute significantly to sustainable soybean production and agricultural diversification in Uzbekistan
Keywords: Soybean; Glycine max; Baraka